2018
DOI: 10.5812/hepatmon.62079
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Serum HBV RNA in Patients with Untreated HBeAg-Positive and -Negative Chronic Hepatitis B Infection

Abstract: Background: The serum hepatitis B virus (HBV) RNA is suggested as a potential new biomarker of HBV infection. However, it is not fully understood. Objectives: The current study aimed at characterizing serum HBV RNA in patients with untreated chronic hepatitis B (CHB) and genotype B and C HBV infection. Methods: A large cohort of 483 patients with hepatitis B e antigen (HBeAg)-positive and -negative was performed. The routine serum biomarkers of HBV infection were tested. HBV genotyping was carried out by direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…In this study, the following correlation analysis results between HBV RNA levels and HBV DNA, HBsAg, ALT, and AST levels in the 149 HBsAg and HBsAb copositive patients were noted: serum HBV RNA levels were all positively correlated with HBV DNA (correlation efficient r = 0.667, P = .000), HBsAg (correlation efficient r = 0.330, P = .000), ALT (correlation efficient r = 0.263, P = .001) and AST levels (correlation efficient r = 0.218, P = .007). The best correlation was noted between HBV RNA levels and HBV DNA levels, which is consistent with previous studies [29–30] . Therefore, HBV RNA can be used as a potential virological marker to assess the efficacy of antiviral therapy in CHB patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the following correlation analysis results between HBV RNA levels and HBV DNA, HBsAg, ALT, and AST levels in the 149 HBsAg and HBsAb copositive patients were noted: serum HBV RNA levels were all positively correlated with HBV DNA (correlation efficient r = 0.667, P = .000), HBsAg (correlation efficient r = 0.330, P = .000), ALT (correlation efficient r = 0.263, P = .001) and AST levels (correlation efficient r = 0.218, P = .007). The best correlation was noted between HBV RNA levels and HBV DNA levels, which is consistent with previous studies [29–30] . Therefore, HBV RNA can be used as a potential virological marker to assess the efficacy of antiviral therapy in CHB patients.…”
Section: Discussionsupporting
confidence: 90%
“…The best correlation was noted between HBV RNA levels and HBV DNA levels, which is consistent with previous studies. [ 29 30 ] Therefore, HBV RNA can be used as a potential virological marker to assess the efficacy of antiviral therapy in CHB patients. A recent study indicated that HBV RNA may exhibit a fast and significant decline that correlates with treatment response and HBsAg loss at long-term follow-up during PEG-IFN treatment for HBeAg-negative CHB.…”
Section: Discussionmentioning
confidence: 99%
“…20 Multivariate logistic regression analysis revealed that qHBsAg and HBeAg are factors that influence serum HBV RNA below the lower limit of detection in patients with CHB. In this study, the total detection rate of serum HBV RNA in patients with CHB was 32% (23/72), which was similar to the detection rate in the study by Huang et al 12 However, the detection rate in the study conducted by Li et al 21 was 85.3%. Among other factors, this difference may be due to sample selection, demographic characteristics and variable methodology.…”
Section: Discussionsupporting
confidence: 87%
“…The serum samples of 328 untreated HBeAg-positive Chinese CHB patients with GTB or GTC HBV infection were from our previous registered clinical study (NCT01088009) [ 21 , 22 ]. The informed consents were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Serum level of HBV DNA was quantitated by TaqMan 48 automatic fluorescence quantitative PCR kits using Roche COBAS AmpliPrep/COBAS TaqMan 48 Analyzer (Roche Diagnostics, Mannheim, Germany) [ 22 ]. Serum level of HBV RNA was quantitated by our published in-house assay [ 21 ].…”
Section: Methodsmentioning
confidence: 99%